New Orders and Asset Prices - Jones, Christopher S.; Tuzel, Selale (Review of Financial Studies, 2013)
This paper investigates the behavior of the ratio of new orders to shipments of durable goods (NO/S). High levels of NO/S are associated with a business cycle peak. They predict a short-run increase in employment and fixed and inventory investment but a dramatic long-run decline in employment, fixed investment, inventories, and GDP as a whole. We also find that NO/S captures time-varying risk premia. Higher levels of NO/S forecast lower excess returns on a broad set of assets, including equities, longand intermediate-term Treasury bonds, and high- and low-grade corporate bonds, at horizons from one month to one year. These effects are robust to the inclusion of all common return predictors. We then construct an equilibrium model of investment with time to plan and a countercyclical price of risk which implies that the ratio of new orders to shipments is procyclical and predicts lower excess returns.